Factors associated with perception and expectations to work in the area of primary health care at five facilities of the first level care in Lima, Peru - Inga Berrospi, Fiorella (2020)
Aim: To identify the frequency of perception and expectations to work in the area of primary health care(PHC) as well as theirassociated factors with personnel at five health facilities. Method: Cross-sectional study on five health facilities of PHC. Perception and expectations to work in PHC were measured, and their association with social-work variables was investigated. Simple and multiple regression analysis was performed to estimate prevalence ratios (PR), using the Poisson family, robust variance and having a health facility as a cluster. Results: Out of 94 participants, 64.9% did not have an adequate perceptionabout working in the area of PHC. The 60.6% had an expectation to work in PHC 10 years from now. A positive association was found between female gender and perception about working in the area of PHC (PR = 3.24). There was a negative association between being divorced and/or widowed and the expectation to work in PHC (PR: 0.51). Conclusions: Perception about working in PHC is low, but more than half of the sample expect to work in PHC10 years from now. Being a woman increases the prevalence job perception in PHC. Working time over 5 years was positively associated with having expectations to work in PHC. On the contrary, divorced/widowed marital status was negatively associated.